Maireinfra 2023 2023
DOI: 10.3390/engproc2023036012
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a Sustainable and Innovative Solution for Unpaved Rural Roads

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Building a sustainable future necessitates a shift in mindset from short-term gains to long-term benefits, from exploitative practices to regenerative ones, and from individualism to collective action. It requires the adoption of innovative technologies, the promotion of sustainable consumption and production patterns, and the empowerment of marginalized communities [8][9][10]. Furthermore, it demands the integration of sustainability principles into education, research, policymaking, and governance processes of education, enabling holistic and inclusive approaches to sustainable development [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Building a sustainable future necessitates a shift in mindset from short-term gains to long-term benefits, from exploitative practices to regenerative ones, and from individualism to collective action. It requires the adoption of innovative technologies, the promotion of sustainable consumption and production patterns, and the empowerment of marginalized communities [8][9][10]. Furthermore, it demands the integration of sustainability principles into education, research, policymaking, and governance processes of education, enabling holistic and inclusive approaches to sustainable development [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Infrastructures 2023, 8, 144 2 of 13 Reclaimed asphalt (RA), obtained from the milling of existing asphalt pavements, and mineral sludge (MS), derived from the industrial washing of natural aggregates in crushing plants, may be effectively used as alternative aggregates in the construction of pavement layers as a consequence of their high availability and due to the possibility of solving problems concerning their stockpiling and/or disposal [39,45,46]. In particular, a previous research study conducted by the authors showed that RA and MS could be successfully employed in large quantities in the production of emulsion-based cold recycled mixtures (CRMs) for the surface finishing of unpaved rural roads [47,48].…”
Section: Introductionmentioning
confidence: 99%